The person and the Inter-American Court of Human Rights - Alburqueque Uceda, Silvia Johanna (2018)
The Inter-American Court of Human Rights (Inter-American Court of Human Rights) has had, within the Inter-American Human Rights System, the important function of guaranteeing respect and protection of human rights of individuals in the face of possible arbitrary action by the States, which may injure, prevent or hinder the exercise of them. Thus, the Court's performance has been for many years, a fundamental instrument for the correct application of the rights embodied in the Convention, which has had as its center of action, the human person. However, in recent years, the Court has taken a quite noticeable turn in relation to the interpretation of the rights that the Convention defines and defends, through sentences in which it has come to disrupt the core of protection of basic and elementary rights, as the right to life, to identity, to non-discrimination, which, according to our analysis, would affect, mainly, the person’s development from an objective and integral view, with the emergence of serious consequences, that would expose the Court to cease being an important mechanism of legal protection to become a mechanism of expansion of ideologies contrary to the person itself.